Analisis Perkembangan Inventasi di Provinsi Papua Barat Tahun 2011-2015 - Elina R. Situmorang; Naftali Mansim; Nuur Rohmi Permatasari (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2018)
This research aims to describe the investment growth in Papua Barat between 2011 and 2015, and to analyse the potential sectors related to the growth of investment. Data used in this research was secondary data sourced from Badan Penanaman Modal dan Pelayanan Perizinan Terpadu (BPMP2T) of Papua Barat. Data was then analysed using descriptive tabulation method. The results indicated that the realisation of domestic investment in Papua Barat increased from 2011 to 2015. This is because the administrative processes in terms of investment licensing were getting better in this province. The results also highlighted that the realization of foreign investment in Papua Barat was fluctuative, and even more likely to decrease during the similar period. In addition, the findings also indicated that the potential sector that had the highest domestic investment was palm oil plantation sector in Sorong regency, and the potential sector that had the highest foreign investment was general mining sector in Raja Ampat regency.